Work-based learning as a catalyst for sustainability: a review and prospects. Issue 2 (8th May 2017) - Wall, Tony; Hindley, Ann; Hunt, Tamara; Peach, Jeremy; Preston, Martin; Hartley, Courtney; Fairbank, Amy
Abstract : Purpose: The purpose of this paper is to highlight the continuing dearth of scholarship about the role of work-based learning in education for sustainable development, and particularly the urgent demands of climate literacy. It is proposed that forms of work-based learning can act as catalysts for wider cultural change, towards embedding climate literacy in higher education institutions. Design/methodology/approach: This paper draws data from action research to present a case study of a Climate Change Project conducted through a work-based learning module at a mid-sized university in the UK. Findings: Contrary to the predominantly fragmented and disciplinary bounded approaches to sustainability and climate literacy, the case study demonstrates how a form of work-based learning can create a unifying vision for action, and do so across multiple disciplinary, professional service, and identity boundaries. In addition, the project-generated indicators of cultural change including extensive faculty-level climate change resources, creative ideas for an innovative mobile application, and new infrastructural arrangements to further develop practice and research in climate change. Practical implications: This paper provides an illustrative example of how a pan-faculty work-based learning module can act as a catalyst for change at a higher education institution. Originality/value: This paper is a contemporary call for action to stimulate and expedite climate literacy in higher education, and is the first to propose that certain forms of work-based learning curricula can be a route to combating highly bounded and fragmented approaches, towards a unified and boundary-crossing approach.